The Relation between Epstein-Barr Virus and Hodgkins Disease: lmmuno-histo- pathological Analysis of EBV LMP-1 expression) - C. Murtono, C. Murtono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
EBV-LMP-1 is one of the proteins formed in the B lymphocytes and that has an oncogenic property and expressed by Sternberg Reeds cells. Detection of EBV LMP-1 is a reliable method to determine the presence of EBV in Hodgkins disease. There were geographical distributions of Hodgkins disease based on its histological classification. This study determined the correlation between EBV and Hodgkins disease based on its histological subtype in Yogyakarta. Eighteen formaldehyde fixed in paraffin wax embedded specimen of Hodgkins disease were investigated for their EBV-LMP-1 expression by immunohistochemistry reaction with cocktail CS 1-4 (DAKO) as monoclonal antibody and Mayers Hematoxillin as counterstain. For negative control LMP-1 monoclonal antibody was omitted. EBV LMP-1 expression was detected in 9/18 (50%) of Hodgkins disease cases. The frequency of Hodgkins disease subtypes is as follows LP (lymphocytic predominance) 11.11%, NS (nodular sclerosis) 11.11%, MC (mixed cellularity) 22.22% and LD (lymphocytic depletion) 55.55%. The median age of the patients is 52.5 years with mean 52.3 year and SD 9.15 year. LMP-1 positivity was detected in 0/2 (0%) for LP subtype, 1/2 (50%) for NS, 2/4 (50%) for MC, and 6/10 for LD (60%). Based on EBV LMP-1 expression in the Sternberg Reed cells, it corroborated a significant role for EBV on the oncogenesis of Hodgkins disease in Yogyakarta especially for LD subtypeKey Words : Hodgkins disease - histological classification - latent membrane protein-1 (LMP-1) -immunohistochemistry - oncogenesis.